2022
DOI: 10.1136/bmjopen-2022-066015
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional risk factors for all-cause mortality of critically ill patients: a retrospective cohort study

Abstract: ObjectivesThis study aimed to explore the predictive value of single and multiple risk factors for the clinical outcomes of critically ill patients receiving enteral nutrition and to establish an effective evaluation model.DesignRetrospective cohort study.SettingData from the 2020–2021 period were collected from the electronic records of the First Affiliated Hospital, Nanjing Medical University.Participants459 critically ill patients with enteral nutrition in the geriatric intensive care unit were included in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In a recent report on more than 6,000 adults with sepsis, greater than 20% of cases presented with hypothermia-a conservative number given that normothermia was defined as a temperature greater than or equal to 35.6°C (54). Similarly, a recent study of more than 1,000 children found that hypothermia (< 36.5°C) at admission was observed in 13.6% of cases (55). A possible role for CSR was not discussed in either report.…”
Section: Role Of the Csr Beyond Neuroprotection In Pediatric Critical...mentioning
confidence: 89%
“…In a recent report on more than 6,000 adults with sepsis, greater than 20% of cases presented with hypothermia-a conservative number given that normothermia was defined as a temperature greater than or equal to 35.6°C (54). Similarly, a recent study of more than 1,000 children found that hypothermia (< 36.5°C) at admission was observed in 13.6% of cases (55). A possible role for CSR was not discussed in either report.…”
Section: Role Of the Csr Beyond Neuroprotection In Pediatric Critical...mentioning
confidence: 89%
“…22 In a study in pediatric patients, extremes of temperatures have been associated with worse outcomes in sepsis. 23 Interventions aimed to correct or induce hypothermia have yielded different results. In a study of patients with cardiogenic shock receiving venoarterial extracorporeal membrane oxygenation, moderate hypothermia for 24 h compared with normothermia did not significantly decrease 30-day mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research have shown that the ratio of PCT and CRP to indicators such as serum prealbumin or erythrocyte sedimentation rate (ESR) has clinical significance in the diagnosis, management, and prognosis, such as the study by Christopher et al (2021), which showed that ESR/CRP helps to determine the duration of periprosthetic joint infection and informs the physician's treatment choice. Another study showed that serum prealbumin/PCT was negatively associated with time in intensive care and death, and could be used as an indicator of patient severity and short-term prognosis (Wang et al, 2022). Given the high and low variability of PCT, CRP, and SDI in the context of bacterial infection in patients, the ratio of inflammatory indexes to SDI was used exploratively in this study.…”
Section: Discussionmentioning
confidence: 99%